Dihydromyricetin suppresses inflammatory responses in vitro and in vivo through inhibition of IKKβ activity in macrophages. Issue 6 (3rd August 2016) - Wang, Rui; Pi, Jiang; Su, Xiaohui; Liu, Juan; Zeng, Xing; Wong, Ivan; Huang, Lufen; Zhou, Hua; Cai, Jiye; Li, Ting; Liu, Liang
Summary: Dihydromyricetin (DMY) a flavonoid derived from medicinal plant Ampelopsis grossedentata, possesses anti‐oxidative and anti‐inflammatory effects in vitro, however, the in vivo anti‐inflammatory action of DMY remains unknown. In the current study, carrageenan‐induced paw edema in rat, an acute inflammation model, and RAW264.7 macrophages activated by LPS were employed to evaluate the anti‐inflammatory potency of DMY in vivo and in vitro . Results showed that DMY significantly attenuated rat paw edema induced by carrageenan. Also, DMY markedly inhibited NO secretion, iNOS, and COX‐2 protein expression, as well as p65 phosphorylation via suppression of IKKβ activity and IKKα/β phosphorylation in RAW264.7 cells. And using high resolution Atomic Force Microscope (AFM), we also proved that DMY prevented morphological change and membrane alterations of RAW 264.7 macrophages caused by LPS stimulation. As activation of macrophages is one of major factors in carrageenan‐induced paw edema of rats, the anti‐inflammatory action of DMY is suggested to be closely associated with suppression of macrophage activation. These findings indicate that DMY is valuable of being further investigated as a candidate new agent for treating inflammatory conditions, and suggest that AFM could be a powerful nanotool for anti‐inflammatory investigations. SCANNING 38:901–912, 2016. © 2016 Wiley Periodicals, Inc.